French negotiation style: A qualitative approach - Rendón, María Isabel; Fosse, Sebastien; Ogliastri, Enrique (Pontificia Universidad Javeriana, 2017)
Based on theories developed by Hall,Hofstede,and the Globe project,this article analyzes,on one hand,the patterns of French negotiators,and on the other hand,the challenges that people from other cultures face when they negotiate with the French. Inductive,comparative and qualitative methodologies are used about specific negotiation experiences with the French: a focus group and three studies with semi-structured interviews with 244 negotiators from five continents. To those negotiating with the French,it is advised to prepare negotiations with facts,figures and solid arguments,to look for a gradual approach,to be assertive but flexible,and to maintain formality and good manners at the negotiation table. © 2017,Pontificia Universidad Javeriana. All rights reserved.
[Négociation à la Française: Une approche qualitative]
[Negociación a la francesa: Un enfoque cualitativo]
Keywords: Culture; France; Latin America; Negotiation; Qualitative methods; 63 Sociología::6301 Sociología cultural; ODS 17 - Alianzas para lograr los objetivos